Rebranding of campbell complex and impact toward its brand equity / Muhd Hafiz Ramli - Ramli, Muhd Hafiz (2012)
Maintaining strong brand equity is not an easy task for the organization. Without proper planning and strategy, the brand might face lots of trouble. The same goes to the Campbell Complex. This shopping complex used to be very famous in the backdays. But now the situasion is not the same anymore. The new management of Campbell Complex currently is worried about this situation. Therefore they had decided to rebrand the Campbell Complex but at the same time maintaining the advantage of this shopping complex. This study was done for the purpose to clarify the rebranding concepts and investigated the influences of rebranding toward brand equity. Structured questionnaire was used in this study. 110 questionnaires were distributed to the tenants and customers of Campbell Complex. Based on the analysis, it was found that rebranding (internal branding, repositioning, brand name and online advertising) influences brand equity. All concepts was found positively influenced brand equity